Gender Equality Perceptions of Future Engineers. Issue 3 (2nd September 2019) - Pla-Julián, Isabel; Díez, Jose-Luis
Abstract : Gender bias is important in our society not only from the point of view of ethics and human rights but also from a pragmatic engineering point of view. Universities are aware of this issue and develop equality plans, some of them including specific actions like education in gender equality. We ask, how effective are these actions? And, are there any differences in the perception of gender equality between social sciences/humanities and engineering university students? In order to answer these questions, a case study of the Spanish university system was carried out by comparing equality perception in the students of two universities: the Universidad de Valencia Estudio General and the Universitat Politècnica de València. For this purpose, 338 questionnaires were filled in by university students and were processed in two academic years (2015/2016 and 2016/2017), and at two different moments: before (225) and after (113) receiving a gender equality course. Results show the main differences in gender perception among Engineering and Social Sciences students, and the importance of gender courses.